Alternative of Coastal Erosion Countermeasures in Bungin, Luwuk District, Banggai Regency - Susilawati, Sri; Mefianti, Desi (Universitas Negeri Semarang, 2018)
This study aims to determine the most effective countermeasures in protecting and controlling abrasion along the coast in Bungin village, Luwuk district, Banggai regency. The data collection technique used is observation technique using tidal data to determine the water level of the plan and the elevation of the light and the wind data. The analysis showed that the wave happened in Bungin villages not too bigÂ since the significant wave height is 0.4553 m with wave period (Ts) 2.6754 seconds. Although the wave is not significantly big, it still needs attention given the fact that this coastal border area is a residential area where the location of a near future road project is located very close to the coastline. The revetment is an alternative to the coast protection system which is considered as effective and efficient to anticipate this issue. This alternative has mercu elevation +2,214, water level design + 0,914 and building elevation -0,850 with height 4,20 metersand length of this coastâ€™s safety building is 2188,225 meters. The height of coast safety layer is 0,75 meterswith width 2,20 metersand weight of safety stonesis 0,028 tons.